Influence of Eu3+-Doped on Phase Transition Kinetics of Pseudoboehmite - Fuliang Zhu; Yanshuang Meng (Advances in Materials Science and Engineering)
The influence of Eu3+-doped on phase transition kinetics of pseudoboehmite has not been reported in the literature. Through dropping Eu(NO3)3 into pseudoboehmite colloidal solution, pseudoboehmite xerogel was produced using spray pyrolysis. The influence of Eu3+-doped on the mechanism of pseudoboehmite phase transition kinetics has been calculated and analyzed by TG/DSC, XRD, and Kissinger equation. Part of Eu3+ ion formed compound EuAl12O19, which existed between α-Al2O3 grains. Bulk diffusion of Al3+ was prevented from compound EuAl12O19. Therefore, phase transition kinetics rate of θ-Al2O3 → α-Al2O3 was slowed down, causing an increase of phase transition activation energy and elevation of phase transition temperature.